2022
DOI: 10.1002/jsfa.12227
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism leading to color differences between purple‐red and green partridge tea leaves

Abstract: Background: Partridge tea (Mallotus oblongifolius) is used as an important beverage and medical plant in Hainan province of China. Although some information about the morphology, cytology, and genetics of partridge tea has been reported in the literature, knowledge about this plant is still very limited. The leaves are the most important part for every tea plant, with a major role in nutrition and other functions. The leaves of different cultivars of partridge tea are different in colors and functions. The mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Compared with NPFL samples, the metabolites of isoquercitrin and astragalin involved in flavone and flavonol biosynthesis and the metabolites of (−)-EGC and (−)-GC involved in flavonoid biosynthesis were UP-regulated in LPFL and HPFL samples (Figure ). As these metabolites are essential for anthocyanin synthesis, the difference in the anthocyanin content may be the cause of the color differences. , In addition, many studies showed that the flavonoid metabolic pathway or flavone and flavonol metabolic pathway is among the main enrichment pathways of tea plants under cold and drought stress, , indicating that products of these biosynthetic pathways play a positive role in plant stress resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with NPFL samples, the metabolites of isoquercitrin and astragalin involved in flavone and flavonol biosynthesis and the metabolites of (−)-EGC and (−)-GC involved in flavonoid biosynthesis were UP-regulated in LPFL and HPFL samples (Figure ). As these metabolites are essential for anthocyanin synthesis, the difference in the anthocyanin content may be the cause of the color differences. , In addition, many studies showed that the flavonoid metabolic pathway or flavone and flavonol metabolic pathway is among the main enrichment pathways of tea plants under cold and drought stress, , indicating that products of these biosynthetic pathways play a positive role in plant stress resistance.…”
Section: Resultsmentioning
confidence: 99%
“…As these metabolites are essential for anthocyanin synthesis, the difference in the anthocyanin content may be the cause of the color differences. 22,23 In addition, many studies showed that the flavonoid metabolic pathway or flavone and flavonol metabolic pathway is among the main enrichment pathways of tea plants under cold and drought stress, 13,24 indicating that products of these biosynthetic pathways play a positive role in plant stress resistance. clear separation between the NPDT, LPDT, and HPDT samples in negative ion mode, indicating that there were differences in the nonvolatile metabolites of NPDT, LPDT, and HPDT.…”
Section: Analysis Of the Nonvolatile Differential Metabolites In Fres...mentioning
confidence: 99%